Drug efflux systems and antibiotic resistance in Burkholderia pseudomallei - Trunck, Lily, author; Schweizer, Herbert P., advisor (Colorado State University. Libraries, 2009)
Burkholderia pseudomallei, the etiologic agent of melioidosis, is intrinsically resistant to most antibiotics. A predicted 10 RND efflux transporters are encoded by the B. pseudomallei genome; 3 have been characterized (AmrAB-OprA, BpeAB-OprB, and BpeEF-OprC) as major contributors to the intrinsic aminoglycoside, macrolide, chloramphenicol, and trimethoprim resistance of this organism. AmrAB-OprA is constitutively expressed in most strains and confers resistance to aminoglycosides. Gentamicin susceptible clinical isolates have been identified and work in this dissertation demonstrates that such susceptibility occurs as a result of either insufficient expression or deletion of amrAB-oprA. The mechanisms regulating expression in these strains are unclear, but are not related to mutations in this operon's putative repressor (AmrR) or mutations in the regulatory regions of amrAB-oprA. Expression analysis of seven B. pseudomallei RND efflux pumps (amrB, bpeB, bpeF, bpeH, BPSL0309, BPSL1267, and BPSL1567) in 60 clinical and environmental B. pseudomallei isolates from Thailand demonstrated (i) efflux pump expression is prevalent in both clinical and environmental strains (ii) bpeH is expressed at a higher level in clinical isolates as compared to environmental isolates and (iii) efflux pump expression correlates with resistance/susceptibility to several antibiotics. These data suggest possible substrates for uncharacterized efflux pumps or, alternatively, co-regulation of resistance determinants. Since a deficit in efflux resulted in susceptibility to otherwise clinically useful drugs and that expression of efflux pumps was prevalent in B. pseudomallei, we suggest that efflux pump inhibitors would broaden the spectrum of antibiotics useful for treatment of melioidosis. To facilitate discovery and characterization of such compounds, we have developed a panel of efflux deficient B. thailandensis strains that express the B. pseudomallei efflux pumps, amrAB-oprA and bpeAB-oprB, which can be handled under BSL2 conditions. When expressed in the surrogate background, these pumps have the same substrate profile and can be inhibited by clinically insignificant efflux pump inhibitors to a degree similar to that observed in the native background. In summary, we have assessed the contribution of efflux to antibiotic resistance in B. pseudomallei and described a tool for discovery and characterization of efflux pump inhibitors for pumps expressed in this organism.
Keywords: aminoglycoside; antibiotic resistance; drug efflux; melioidosis; microbiology